Association Between Serum Lipid Levels and Patients With Primary Angle-Closure Glaucoma in China: A Cross Sectional, Case–Control Study - Shao, Mingxi; Li, Yingzhu; Teng, Jisen; Li, Shengjie; Cao, Wenjun (Frontiers in Medicine, 2021)
Objective: To evaluate the serum lipid levels of patients with primary angle-closure glaucoma (PACG) and to investigate the relationship between serum lipid levels and PACG. Methods: In this cross-sectional, case–control study, a total of 320 PACG subjects and 242 age- and sex-matched control subjects were recruited. Serum high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), small dense LDL-C (SDLDL-C), triglyceride (TRIG), and cholesterol (CHOL) levels were measured using enzymatic colorimetry. Serum apolipoprotein A (APOA), apolipoprotein B (APOB), apolipoprotein E (APOE), and lipoprotein(a) (LPa) levels were measured by immunoturbidimetry. Results: The serum LDL-C, TRIG, HDL-C, APOE, LPa, CHOL, APOB, and APOA levels were significantly higher (p<0.05) in the PACG group than in the control group. Multiple liner regression analyses revealed that there was a statistically correlation between HDL-C levels and mean deviation MD (B=0.389, p=0.002, 95% confidence interval [CI]=-1.249 to -0.624); LDL-C levels and MD (B=0.190, P=0.019, 95% CI=-5.632 to -1.306); and CHOL levels and MD (B=0.364, P=0.27, 95% CI=-7.727 to -1.839). Logistic regression analyses showed that high serum HDL-C (odds ratio [OR]=11.01, 95% CI=5.616 to 21.587), LDL-C (OR=1.330, 95% CI=1.079 to 1.640), SDLDL-C (OR=1.007, 95% CI=1.005 to 1.008), APOA (OR=13.621, 95% CI=7.251 to 25.591), APOB (OR=2.243, 95% CI=1.060 to 4.732), LPa (OR=0.999, 95% CI=0.998 to 1.00), and CHOL (OR=1.131, 95% CI=1.005 to 1.326) levels were significantly associated with PACG. Conclusions: High serum HDL-C, LDL-C, APOA, APOB, LPa, and CHOL levels were associated with PACG.